Isotropic Long Gamma-Ray Bursts From Unbinding Neutron Stars: The Teranova Model - A Cosandey, David (Annals of Mathematics and Physics, 2026)
Long gamma-ray bursts (GRBs), the most luminous explosions in the Universe, are generally explained with the highly anisotropic “jetted-collapsar-seen-head-on” model (collapsar model). We argue that this model has suffered critical experimental setbacks, in particular: non-periodical light curves, quasi-absence of off-axis collapsars, frequent absence of associated supernovae (SNe), weird exclusivity of type 1c/1b SNe, unexplainable ultra-long GRBs, not to mention severe internal inconsistencies. To overcome these issues, we call for a paradigm change. We suggest modelling long GRBs as isotropic explosions powered by unbinding neutron stars (NSts). Indeed, neutron stars possess binding energies that are in line with isotropic energy levels of bursts. We argue that such tremendous NSt explosions (“teranovae”) may occur during collisions between high-velocity (HV) magnetars and blue supergiant stars. Such collisions have a much more chances to occur in high-density blue galaxies, where indeed most bursts are observed. A HV magnetar punching into a supergiant star enters extreme super-Eddington mode, attracting 5-10 M⊙ or more into its accretion torus in a short time. The disk heats the central NSt, which reaches unbinding temperature and explodes within the host star. The detonation blows away the supergiant’s external layers, creating the H&He stripped core necessary for the ensuing 1c-SN. When the core is smashed into pieces or left behind the optically thick ejecta, we witness a SN-lacking long GRB. We show that this model fits nicely with most observational data. In particular, we seamlessly integrate the ultra-long GRBs into the framework, we interpret the relativistically-expanding spherical afterglow bubbles naturally, we explain the supernovae blueshifts, we find the creation mechanism for the SN-1c progenitors, and we reconcile kilonova-having long bursts and SN-having short bursts in a unified theory.